2005
DOI: 10.1016/s0002-9440(10)62985-9
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Estrogen Receptor-α-Positive Mammary Epithelial Cells Is Restrained by Transforming Growth Factor-β1 in Adult Mice

Abstract: Transforming growth factor (TGF)-beta1 is a potent inhibitor of mammary epithelial proliferation. In human breast, estrogen receptor (ER)-alpha cells rarely co-localize with markers of proliferation, but their increased frequency correlates with breast cancer risk. To determine whether TGF-beta1 is necessary for the quiescence of ER-alpha-positive populations, we examined mouse mammary epithelial glands at estrus. Approximately 35% of epithelial cells showed TGF-beta1 activation, which co-localized with nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 51 publications
3
88
0
Order By: Relevance
“…The evidence of Ewan et al (2002) is suggestive of a regulatory circuit where estrogen regulates the activation of TGFb, which in turn functionally restrains the proliferative response to hormonal signalling. This is supported by the evidence that steroid receptors (both ER and progesterone receptors) can be frequently colocalized in cells with active TGFb and that this population of cells is generally not proliferative (Zeps et al, 1998;Ewan et al, 2002Ewan et al, , 2005. Thus, we can suggest that estrogen controls cell proliferation by an indirect mechanism where ER positive cells, when exposed to hormonal stimuli, produce growth factors that stimulate the proliferation of adjacent (mainly ER negative) cells (Russo et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The evidence of Ewan et al (2002) is suggestive of a regulatory circuit where estrogen regulates the activation of TGFb, which in turn functionally restrains the proliferative response to hormonal signalling. This is supported by the evidence that steroid receptors (both ER and progesterone receptors) can be frequently colocalized in cells with active TGFb and that this population of cells is generally not proliferative (Zeps et al, 1998;Ewan et al, 2002Ewan et al, , 2005. Thus, we can suggest that estrogen controls cell proliferation by an indirect mechanism where ER positive cells, when exposed to hormonal stimuli, produce growth factors that stimulate the proliferation of adjacent (mainly ER negative) cells (Russo et al, 1999).…”
Section: Discussionmentioning
confidence: 72%
“…It has been proposed that estrogen and TGFb act in a regulatory circuit where estrogen modulates the activation of TGFb which in turn regulates the proliferative response to estrogen (Ewan et al, 2002(Ewan et al, , 2005. Following our identification of CITED1 among a group of genes whose expression was specifically upregulated in the pubertal mouse mammary gland, we hypothesized that CITED1 acted to mediate signals from both estrogen and TGFb in accordance with its previously elucidated mechanism of action.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…In order to explore the relationship between proliferation and both ERα and TGF-β signaling, ewan and colleagues sought to determine their expression in mouse mammary glands at estrus, and discovered co-localization with phosphorylated Smads and nuclear ERα. This indicated a co-regulation of the pathways and suggested that TGF-β could act to restrict ERα-mediated proliferation [230]. Furthermore, the proliferation rate of mammary gland cells was significantly increased in a mouse model of heterozygous TGF-β1 expression and proliferation marker Ki67 expressing cells frequently coexpressed ERα.…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 92%
“…This dissociation of proliferation and HR expression was subsequently demonstrated in vivo, both in mice and in rats 50,51 , and this led to the suggestion that HR + cells function as organizers that may instruct their neighbours. The low propensity of HR + cells to proliferate has been linked to the presence in the subjacent extracellular matrix (ECM) of processed transforming growth factor-β (TGFβ) that activates TGFβ receptor (TGFβR) signalling, leading to the accumulation of phosphorylated SMAD2 and SMAD3 in the nucleus 52 .…”
Section: Cellular Mechanisms Of Steroid Actionmentioning
confidence: 99%